Design an Ozone Generator by Using Dielectric Barrier Discharge - Al-Jobouri, Hamid H; Ismaeel, Hadeel O (Al-Nahrain Journal of Science, 2018)
An Ozone generator was designed according to dielectric barrier discharge (DBD) technique with Oxygen as a feed gas for Ozone generating. The effect of the flow rate on the concentration of the Ozone was studied, the flow rate was varied from 0.6 to 5lit/ min for two values of the gap space between electrodes d= 2 and 4 mm, and two values of the electrode area A= 20 and 36 cm2. Also, the effect of the applied voltage on the concentration of the Ozone was studied, the applied voltage was varied from (1- 9 kV) for the same gap space and electrode area values. It is found that the concentration of Ozone produced increases with increasing voltage, and decreases with increasing flow rate.